Educating Labour’s Professionals - Nesbit, Tom (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2001)
SummaryThis study examines the nature of education and training for full-time union staff and officials in Canada and explores some of the factors that affect such provision. It was designed to complement similar studies of other countries and to contribute to more general discussions of labour education. The study compares the opportunities of training for Canadian union staff with similar provision in Britain and the U.S.A. and locates the discussion about further training within the contexts of existing programs of labour education and current debates about the revitalization of the labour movement. The study concludes with a call for more systematic discussion of these issues and analysis of different programmatic models.